PENGARUH IMPLEMENTASI KEBIJAKAN DANA KAPITASI DAN KINERJA TERHADAP KUALITAS PELAYANAN KESEHATAN DI PUSKESMAS CIMAHI TENGAH - Mike Kalora; Barkah Rosadi; Sahromi Sahromi (Journal Publicuho, 2023)
The main problem in this study is the capitation policy in the JKN era through BPJS in the Cimahi Tengah Health Center, Cimahi City in particular, and Indonesia in general, the quality of health services and employee performance have not met expectations. This is caused by the implementation of policies that have not been optimal and knowledge about this capitation policy has not been understood. This study aims to determine the effect of capitation policy implementation and performance on improving the quality of health services in the Cimahi Tengah Community Health Center, Cimahi City. The method in this study is to use a descriptive analysis method, namely by describing each variable and testing both variables with a quantitative (statistical) approach which is then analyzed and compared with existing theories and problems to draw conclusions. Based on the findings in this study, the provision of capitation policies, both material and non-material, needs to be fulfilled so that employees can achieve performance that is in line with organizational expectations. For this reason, it is necessary for the leadership to pay attention to the implementation and application of the capitation system built to achieve organizational goals and objectives.